THU0322 Altered Quality of Life Is Mainly Associated with Patient Reported Outcomes in Primary Sjögren's Syndrome Patients: Data from A Large Therapeutic Trial. (15th July 2016) - Cornec, D.; Devauchelle-Pensec, V.; Mariette, X.; Jousse-Joulin, S.; Berthelot, J.-M.; Perdriger, A.; Puéchal, X.; Le Guern, V.; Sibilia, J.; Gottenberg, J.-E.; Chiche, L.; Hachulla, E.; et al.
Abstract : Objectives: To identify the main determinants of quality of life (QoL) alteration in patients with active primary Sjögren's syndrome (pSS) participating in a large therapeutic trial. Methods: At the inclusion visit in the TEARS trial, 120 patients with active pSS completed the Short Form survey 36 (SF36), a validated tool measuring the level of QoL. The association of demographic data, patient-reported outcomes (including the EULAR SS Patient Reported Index (ESSPRI) score), objective measurements of dryness and autoimmunity, and the physician evaluation of systemic activity (using the EULAR SS Disease Activity Index (ESSDAI) score) with SF36 physical and mental components were assessed by univariate then multivariate linear regression analyses. Results: SF36 results showed a marked alteration of QoL in this population of patients with active pSS. The strongest predictors of a low QoL (for both physical and mental components, Table 1 ) were patient-reported symptoms, best assessed using the ESSPRI, with pain and ocular dryness intensity displaying independent association with QoL. Conversely, systemic activity level was not associated to QoL alteration, even in the subset of patients with moderate to high systemic activity as defined by the ESSDAI. Conclusions: pSS cardinal symptoms (dryness, fatigue and pain) are the major predictors of QoL alteration and should be targeted in future therapeutic trials in addition to systemic involvement. Disclosure of Interest: None declared